Electric and magnetic tuning of Gilbert damping constant in LSMO/PMN-PT(011) heterostructure. (19th July 2023) - Das, Avisek; Mrinalini,; Usami, Takamasa; Prakash Pati, Satya; Taniyama, Tomoyasu; Gorige, Venkataiah
Abstract: Electric field control of magnetodynamics in magnetoelectric (ME) heterostructures has been the subject of recent interest due to its fundamental complexity and promising applications in room temperature (RT) devices. The present work focuses on the tuning of magnetodynamic parameters of epitaxially grown ferromagnetic (FM) La0.7 Sr0.3 MnO3 (LSMO) on a ferro(piezo)electric (FE) Pb(Mg0.33 Nb0.67 )O3 -PbTiO3 (PMN-PT) single crystal substrate. The uniaxial magnetic anisotropy of LSMO on PMN-PT confirms the ME coupling at the FM/FE heterointerface. The magnitude of the Gilbert damping constant ( α ) of this uniaxial LSMO film measured along the hard magnetic axis is significantly small compared to the easy axis. Furthermore, a marked decrease in the α values of LSMO at positive and negative electrical remanence of PMN-PT is observed, which is interpreted in the framework of strain induced spin dependent electronic structure. The present results clearly encourage the prospects of electric field controlled magnetodynamics, thereby realising the RT spin-wave based device applications with ultra-low power consumption.